Dielectric Temperature Stability and Enhanced Energy-Storage Performance of Sr0.4Ba0.6(Zr0.2Ti0.2Sn0.2Ta0.2Nb0.2)2O6 High-Entropy Ferroelectric Ceramics - Yingying Zhao; Ziao Li; Shiqiang Yang; Pu Mao; Ruirui Kang (Crystals)
In this research, we employed a high-entropy approach in tungsten-bronze-structured ferroelectric ceramics, preparing Sr0.4Ba0.6(Zr0.2Ti0.2Sn0.2Ta0.2Nb0.2)2 (denoted as SBN40-H) ceramics through the traditional solid-state reaction technique. By utilizing the high-entropy approach, the resulting SBN40-H ceramics demonstrated extremely fine grains, averaging 0.58 μm in size. Furthermore, these ceramics possessed a high bandgap of 3.35 eV, which, when combined with the small grain size, contributed to a remarkable breakdown strength of 570.01 kV/cm. The dielectric characteristics demonstrated typical relaxation behavior and outstanding temperature stability, with a capacitance temperature coefficient (TCC) of less than 5% within the temperature range of 111–317 °C. Additionally, the SBN40-H ceramics exhibit slim P–E loops with negligible hysteresis, which is considered to be related to the existence of weakly coupled relaxors. This results in exceptional overall energy-storage properties in the SBN40-H ceramics, exhibiting a notable recoverable energy density (Wrec) of 2.68 J/cm3 and an efficiency (η) of 93.7% at 390 kV/cm, and finally achieving a remarkable temperature stability in terms of energy-storage performance with variations in Wrec and η being less than 3.5% and 4.4% from 25 to 150 °C. It is worth noting that the high-entropy approach is highly effective in reducing grain size, increasing the breakdown field strength and enhancing the dielectric temperature stability of tungsten-bronze-structured ferroelectric ceramics.